Influence of tourism on the spatial development of seaside resorts: selected aspects - Durydiwka, Małgorzata; Duda-Gromada, Katarzyna (Turyzm/Tourism, 2014)
The paper presents the main trends in the development of seaside resorts worldwide and in Poland. Particular attention is called to the spatial aspects of this development. Based on their morphological differentiation, two forms of seaside resort in Poland can be distinguished: locations with a clearly heterogeneous spatial-functional structure, in which areas used for tourism are adjacent to others; and locations with a heterogeneous spatial-functional structure in which the tourism function is, to a certain extent, spatially isolated.